Building a Knowledge-Based Economy through “Sciencing”: The University of Abuja Students’ Experiences - Aregbesola1, B.G; Barau, Y; Abdulkarim, A (Researchparks Publishing, 2025)
This study explores building a knowledge-based economy through “sciencing”: the University of Abuja students’ experiences with a focus on developing critical thinking, problem-solving, and technical skills in students. The research aims to evaluate how